2018
DOI: 10.1039/c8py00612a
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-isopropenyl-2-oxazoline) as a versatile platform towards thermoresponsive copolymers

Abstract: Thermoresponsive (co)polymers with LCST behavior based on a well-defined PiPOx scaffold showing high versatility in tuning up the TCP as well as the interval of response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 34 publications
0
89
0
1
Order By: Relevance
“…Due to this LCST-type phase transition, such PGEs are soluble in aqueous media below a critical temperature, whereas they undergo a coil-to-globule transition to form turbid solutions when the temperature is raised above their so-called cloud point temperature (CPT). Similar to various POx and POEGMA copolymers [ 42 , 43 ], the CPT of thermoresponsive PGEs can be adjusted via the GME:EGE comonomer ratio and the sharp phase transition is fully reversible and exhibits little to no thermal hysteresis [ 19 , 39 , 40 , 44 ]. In addition, PGEs exhibit a concentration-dependent as well as a strongly molecular weight-dependent CPTs in the range between 1 and 30 kDa [ 39 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to this LCST-type phase transition, such PGEs are soluble in aqueous media below a critical temperature, whereas they undergo a coil-to-globule transition to form turbid solutions when the temperature is raised above their so-called cloud point temperature (CPT). Similar to various POx and POEGMA copolymers [ 42 , 43 ], the CPT of thermoresponsive PGEs can be adjusted via the GME:EGE comonomer ratio and the sharp phase transition is fully reversible and exhibits little to no thermal hysteresis [ 19 , 39 , 40 , 44 ]. In addition, PGEs exhibit a concentration-dependent as well as a strongly molecular weight-dependent CPTs in the range between 1 and 30 kDa [ 39 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The second notable difference between the partially modified PiPOx (PiPOx‐Ax) copolymers and the fully modified (AAc‐Ax) copolymers is that the T CP 's of the fully modified copolymers are lower, for example, 64.8 °C versus 45.3 °C for copolymers with 20 mol % APr, 58.5 °C versus 34.6 °C for copolymers with 15 mol % ABu and 77.6 °C versus 42.6 °C for copolymers with 12 mol % AiBu, respectively . This observation is in accordance with the more hydrophobic character of the acetyl ester amide functionality as compared to the 2‐oxazoline ring as indicated by the LCST behavior of the PiPOx fully modified with acetic acid, which increases the overall hydrophobicity of the polymer and decreases the transition temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction temperature was chosen according to our previous studies regarding the ring opening addition reaction of PiPOx with different monocarboxylic acid to ensure a quantitative conversion of the 2-oxazoline rings and an optimum reaction time. 53,58 FT-IR analysis was used to investigate the chemical structure of the dry polymer networks. The FT-IR spectrum of PiPOx displayed the characteristic signals of the 2-oxazoline ring at 1648 cm -1 (C=N stretching) and 1121 cm -1 (C-O stretching) (see Fig S1).…”
Section: Synthesis and Characterization Of The Pipox Hydrogelsmentioning
confidence: 99%
“…In a recent study, we demonstrated that PiPOx can be chemically modified with mono carboxylic acids yielding soluble thermoresponsive polymers. 53,63 Modulation of the cloud point temperature was achieved by controlling the modification degree and/or by changing the hydrophobic character of the acid.…”
Section: Thermoresponsive Properties Of the H4-h12 Hydrogelsmentioning
confidence: 99%